2019
DOI: 10.1007/s40820-019-0287-8
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite/Silicon Tandem Solar Cells: From Detailed Balance Limit Calculations to Photon Management

Abstract: • Thermodynamic and detailed balance calculations are provided to derive guideline for the optimization of perovskite solar cells. • The influence of photon management on the energy conversion efficiency of perovskite solar cells is discussed. • An optimized solar cell design is proposed, which allows for realizing perovskite/silicon tandem solar cell with an energy conversion efficiency exceeding 32%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 103 publications
(157 reference statements)
0
105
0
Order By: Relevance
“…With a potential application in light emitting diodes [19][20][21], lasers [22][23][24], photodetectors [25][26][27] and other optoelectronic devices, all inorganic lead halide perovskite QDs (IPQDs) could become alternative materials for the down-shifting effect and photovoltaic applications due to their low cost synthesis method, long-time stability, high optical absorption coefficient, as well as controllable and high intensity PL [28][29][30]. Compared with a relatively low PL QY (<50%) in Si QDs [31,32], IPQDs have PL QYs of 80%, 95%, 70%, for red, green, and blue emissions [33].…”
Section: Introductionmentioning
confidence: 99%
“…With a potential application in light emitting diodes [19][20][21], lasers [22][23][24], photodetectors [25][26][27] and other optoelectronic devices, all inorganic lead halide perovskite QDs (IPQDs) could become alternative materials for the down-shifting effect and photovoltaic applications due to their low cost synthesis method, long-time stability, high optical absorption coefficient, as well as controllable and high intensity PL [28][29][30]. Compared with a relatively low PL QY (<50%) in Si QDs [31,32], IPQDs have PL QYs of 80%, 95%, 70%, for red, green, and blue emissions [33].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, PSCs are fabricated on top of a textured silicon solar cell. [8,14,17] A perovskite/silicon TSC is a solar cell in substrate configuration opposite to the superstrate solar cells described in the previous paragraphs of this manuscript. In the remaining section of the manuscript, we focus on solar cells in a substrate configuration.…”
Section: Resultsmentioning
confidence: 99%
“…(TSCs). [14][15][16][17] The hole transport material (HTM) is an essential element for realizing optimum photovoltaic parameters, particularly, the open-circuit voltage (V OC ) of the PSC. Currently, PSCs with high ECEs are made from organic HTMs (e.g., poly (3,4ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), 2,2′,7,7′-tetrakis [N,N-di(4-methoxyphenyl) amino]-9,9′spirobifluorene (Spiro-OMeTAD), poly(triaryl amine) (PTAA), and poly(3-hexylthiophene) (P3HT)), which require additional dopant materials and adhesive ingredients (e.g., bathocuproine (BCP)).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed optical analysis of various TSC structures has demonstrated that optical loss mainly originates from reflection losses and parasitic absorption, especially in perovskite top cells, implying the inherent demands for low absorption in all layers except the absorbers.…”
Section: Optical Loss Analysismentioning
confidence: 99%